An obstruction to subfactor principal graphs from the graph planar algebra embedding theorem. (1st April 2014) - Morrison, Scott
Abstract : We find a new obstruction to the principal graphs of subfactors. It shows that in a certain family of 3‐supertransitive principal graphs, there must be a cycle by depth 6, with one exception, the principal graph of the Haagerup subfactor.